Knowledge and Skills of Senior Architectural Design Students in China: A Channel for Enhancing Future Career Readiness - Zhu, Xiaofei; Layla P.Padolina (International Journal of Social Sciences and Public Administration, 2024)
This chapter presents the findings of the study regarding the assessments of senior architectural design students' knowledge and skills from the perspectives of both the students and employers. The aim is to provide a comprehensive overview of the respondents’ evaluations in various domains critical to architectural education and practice. This paper adopts descriptive quantitative with qualitative data to study the knowledge and skills of architectural design students from different perspectives of architectural design students and design firms (employers) to address deficiencies in key areas of architectural education and practice. In terms of knowledge level evaluation, architectural design students and architectural design companies (employers) evaluate key areas such as design skills, technical knowledge, theoretical understanding, sustainable development awareness and communication skills, and their degree is at a medium level (I). In terms of skill level assessment, architectural design students and architectural design companies (employers) evaluated specific abilities in design skills and creativity, technical ability, project management, sustainable design, and communication and presentation skills, and their levels were at the proficient level (P). evaluate the knowledge and skills level of Chinese architectural design students and develop a corresponding professional improvement plan.